The Mitsunobu reaction, reimagined - Longwitz, Lars; Werner, Thomas (Science)
Catalytic nucleophilic substitution of alcohols makes organic synthesis greener
Keywords: T2; CSSD

Beyond the molecular movie: Dynamics of bands and bonds during a photoinduced phase transition - Nicholson, C. W.; Lücke, A.; Schmidt, Wolf Gero; Puppin, M.; Rettig, L.; Ernstorfer, R.; Wolf, M. (Science)
Ultrafast nonequilibrium dynamics offer a route to study the microscopic interactions that govern macroscopic behavior. In particular, photoinduced phase transitions (PIPTs) in solids provide a test case for how forces, and the resulting atomic motion along a reaction coordinate, originate from a nonequilibrium population of excited electronic states. Using femtosecond photoemission, we obtain access to the transient electronic structure during an ultrafast PIPT in a model system: indium nanowires on a silicon(111) surface. We uncover a detailed reaction pathway, allowing a direct comparison with the dynamics predicted by ab initio simulations. This further reveals the crucial role played by localized photoholes in shaping the potential energy landscape and enables a combined momentum- and real-space description of PIPTs, including the ultrafast formation of chemical bonds.

A 2D Quantum Walk Simulation of Two-Particle Dynamics - Schreiber, Andreas; Gábris, Aurél; Rohde, Peter P.; Laiho, Kaisa; Štefaňák, Martin; Potoček, Václav; Hamilton, Craig; Jex, Igor; Silberhorn, Christine (Science)
Here, There, Everywhere Random walks are a powerful mathematical method that can be used to simulate certain processes in biology, chemistry, or even the stock market. They present a statistical method for mapping the possible routes that processes can take. Quantum walks are expected to be able to probe multiple paths simultaneously. Quantum walks have been demonstrated for one-dimensional, or straight-line, walks. Now, Schreiber et al. (p. 55 , published online 8 March) demonstrate an optical system that can simulate quantum walks over a two-dimensional system, thereby providing the capability of describing much more complex processes.
Keywords: Multidisciplinary

Nuclei-Induced Frequency Focusing of Electron Spin Coherence - Greilich, A.; Shabaev, A.; Yakovlev, D. R.; Efros, Al. L.; Yugova, I. A.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Science)

Time-Resolved Investigation of Coherently Controlled Electric Currents at a Metal Surface - Gudde, J.; Rohleder, M.; Meier, Torsten; Koch, S. W.; Hofer, U. (Science)
Studies of current dynamics in solids have been hindered by insufficiently brief trigger signals and electronic detection speeds. By combining a coherent control scheme with photoelectron spectroscopy, we generated and detected lateral electron currents at a metal surface on a femtosecond time scale with a contact-free experimental setup. We used coherent optical excitation at the light frequencies ωa and ωa/2 to induce the current, whose direction was controlled by the relative phase between the phase-locked laser excitation pulses. Time- and angle-resolved photoelectron spectroscopy afforded a direct image of the momentum distribution of the excited electrons as a function of time. For the first (n = 1) image-potential state of Cu(100), we found a decay time of 10 femtoseconds, attributable to electron scattering with steps and surface defects.

Mode Locking of Electron Spin Coherences in Singly Charged Quantum Dots - Greilich, A.; Yakovlev, D. R.; Shabaev, A.; Efros, Al. L.; Yugova, I. A.; Oulton, R.; Stavarache, V.; Reuter, Dirk; Wieck, A.; Bayer, M. (Science)
The fast dephasing of electron spins in an ensemble of quantum dots is detrimental for applications in quantum information processing. We show here that dephasing can be overcome by using a periodic train of light pulses to synchronize the phases of the precessing spins, and we demonstrate this effect in an ensemble of singly charged (In,Ga)As/GaAs quantum dots. This mode locking leads to constructive interference of contributions to Faraday rotation and presents potential applications based on robust quantum coherence within an ensemble of dots.
Keywords: Multidisciplinary